Oficinando com jovens: análise de processos de atenção na experiência com jogos digitais - Monte, Washington Sales do (2014)
This research analyzes the forms of attention that we can observe the experience of young people who participate in workshops of digital games in a day-care Center of Mossoró/RN. Presents the digital game as eyeshadow experience cognitive and affective changes the course of at-risk youth distress. The game while in interactive technology a reality, simulators offer creates various digital environments and, through their interfaces, can construct situations for his players, interact, producing their realities in simulations of their capable to potentialize learning processes. The central objective of the research was to analyze the ways of operation of attention processes triggered in young's experience with the digital games. We seek to follow the actions of young people in order to learn about how does the process of attention, as required to the learnings. The methodology employed was the intervention research, a qualitative research in which we observe different moments of the interaction of young people with the games in workshops. The workshops that nurture the subjects involved, oficinandos-young people-and workshop participants-master, teacher Advisor and graduate fellows-, build their own experiences and interactivity with the games. The method of cartography allowed to observe and analyze the interactions in different moments of young's experience with the digital game. As a result, realize cognitive transformations referred to the processes of attention on young people's experience with the digital games. During the trial, we were able to keep track of the modulations in times when the subject/player presents a kind of attention, moving process. In this research, the kind of attention that was present at the beginning of the experience was what is defined as voluntary attention, quite common in subjects with a high dispersion process. It is interesting to realize that that kind of attention does not work so static, because the experience of the players, in direct actions in game situation, they began to experiment with processes involving concentration, focus, distraction, anyway, show us how to walk with their learning, show us attention as a learning experience. We noticed the difference between the forms of the operating of the cognitive processes of attention (distraction, dispersion, perception, focus, concentration), processes that were present throughout the course of the experiment. It is interesting to learn that observe young people playing and the movements they perform makes us understand how they learn and cohabit in a different way, so it is always important to look, mobilising our attention to what each shows us and what they do in the collective. The method of mapping helps us learn how to monitor the movements of attention, in writing of the maps of the route. About the movements of the attention, it is possible to say that the distraction presents itself as an important process for learning, the distracted is not always someone who does not have focus. The dispersion is a process that may not favour the player when seeking a deep experience in the process. The perception presents itself differently for each of the subject/players, when they seek to interact in the environment in order to seek landed the attention in any game. Focus and concentration are happening as process and we rejoice to observe young, before pretty scattered, into shares of game showing are concentrated in phases, in plays. The research touches a delicate problem in actuality, connects with other dramas experienced by young people, when the diagnosis of inattention comes with the idea of hyperactivity and the measures of increasing medicalization of young people. At the end of this work, we feel that just started a walk and we left our contribution, to explain the dynamic movement of the processes of attention on the experience of players in a mental health setting